Fostering university students’ reading and understanding of mathematical text in a flipped classroom approach with a digital marking tool - Rezat, Sebastian (Recent Advances in Mathematics Textbook Research and Development)
Abstract Even in the digital age, learning mathematics at an academic level still requires much interaction with mathematical texts. Understanding and developing disciplinary literacy skills at all levels is an increasing matter of interest.

Beispiele geben, Belege anführen und Daten erheben. Diachrone Untersuchung zur Herstellung empirischer Evidenz - Schuster, Britt-Marie; Georgi, Christopher (Germanistische Linguistik. Genese, Zustand und Zukunft eines Faches im Spiegel der RGL)

A Mach-Zehnder-Modulator based FMCW Lidar Emulator in C-Band - Brockmeier, Jan; Kruse, Stephan; Scheytt, J. Christoph (German Microwave Conference 2025)

„Das Mitschaffen am Werden eines neuen Menschen, einer neuen Zeit“ – katholische Geistliche als (Mit-)Gestalter gesellschaftspolitischer Transformationsprozesse in der Weimarer Republik - Adamik, Julie (Macht und Partizipation in gesellschaftlichen Transformationsprozessen)

Crisis and Creativity: Poetry in Times of Corona - Mildorf, Jarmila (Pandemic Storytelling)

„Klassenfahrt“. Einige Überlegungen zum Begriff des Modells im Kontext einer Kunstvermittlungspraxis zum Thema „Fremde überall“. - Autsch, Sabiene (Impulse 7. Texte und Bilder zur Kunstvermittlung. Ein interdisziplinäres Projekt zur Biennale Venedig 2024.)

„Eine göttliche Offenbarung des Zweifels“- Eine Aushandlung lebendigen Glaubens bei Konklave (Robert Harris) - Ginder, Michelle (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik)

Impulse 7. Texte und Bilder zur Kunstvermittlung. Ein interdisziplinäres Projekt zur Biennale Venedig 2024.

Constellations

Open Space. Der Raum als Mikroformat.

Algorithmische Hyperawareness im Songwriting von Plattform-Musiker:innen. Postdigitale Subjektivität und die Transformation musikkultureller Praktiken auf TikTok und Co. - Godau, Marc; Maxelon, Dominik; Neuhausen, Timo (Auditive Medienkulturen. ‘The Evolution of Sound’? Soundkulturelle Praktiken in Social Media-Mikroformaten)
Keywords: Algorithmen; Musikpraxis; Postdigitalität; Songwriting; TikTok

Young students’ engagement with data to create decision trees - Podworny, Susanne; Biehler, Rolf; Fleischer, Yannik (ZDM – Mathematics Education)
Abstract Statistics and machine learning are critical because they play an essential role in our everyday lives and the careers we may pursue in the future. It may be beneficial to introduce machine learning, such as decision trees (DTs), at an early stage of education. The data-based construction of DTs is an example of a machine learning process, which can be addressed in mathematics or statistics teaching because of relatively low prior knowledge requirements. This paper focuses on investigating how sixth-grade students create and evaluate data-based DTs. The basis is a teaching unit that aims to lay the foundation for machine learning and enhance students’ understanding of the process. We investigate students’ processes in detail while they build DTs with data cards about food items to predict whether a new item is recommendable. After the teaching unit, an interview study examines students’ strategies for creating decision trees. The findings contribute to understanding students’ learning processes and the challenges when working with decision trees.

Social Media Music Theory. Musiktheorie auf Instagram als Teil einer Musikpädagogik im Zeitalter der Postdigitalität - Godau, Marc; Gosmann, Phillip (Auditive Medienkulturen. ‘The Evolution of Sound’? Soundkulturelle Praktiken in Social Media-Mikroformaten)
Keywords: Edugram; Instagram; Musiktheorie; Postdigitalität; Social Media

Beyond One-Shot Explanations: A Systematic Literature Review of Dialogue-Based XAI Approaches - Mindlin, Dimitry; Beer, Fabian; Sieger, Leonie Nora; Heindorf, Stefan; Cimiano, Philipp; Esposito, Elena; Ngonga Ngomo, Axel-Cyrille (Artificial Intelligence Review)
In the last decade, there has been increasing interest in allowing users to understand how the predictions of machine-learned models come about, thus increasing transparency and empowering users to understand and potentially contest those decisions.Dialogue-based approaches, in contrast to traditional one-shot eXplainable Artificial Intelligence (XAI) methods, facilitate interactive, in-depth exploration through multi-turn dialogues, simulating expert conversations. This paper reviews the current state of dialogue-based XAI, presenting a systematic review of 1,339 publications, narrowed down to 14 based on inclusion criteria. We explore theoretical foundations of the systems, propose key dimensions along which different solutions to dialogue-based XAI differ, and identify key use cases, target audiences, system components, and the types of supported queries and responses. Furthermore, we investigate the current paradigms by which systems are evaluated and highlight their key limitations. Key findings include identifying the main use cases, objectives, and audiences targeted by dialogue-based XAI methods, and summarize the main types of questions and information needs. Beyond discussing avenues for future work, we present a meta-architecture for these systems from existing literature and outlined prevalent theoretical frameworks.

Developing a simplified linear-elastic material model for carbon paper applied in the rough rail-wheel contact - Stratmann, Ina; Hoyer, Kay-Peter; Schindler, Christian (Journal of Tribology)
Abstract The contact between two partners can be determined using experimental or numerical methods. For the validation of numerical simulations, appropriate experiments and material models of the contact partners are required. Paper in combination with carbon paper can be used in experiments to detect the area of contact between contact partners. A simplified linear-elastic material model of paper for compression in the thickness direction was developed. To evaluate the material model, it was applied to an exemplary wheel-rail contact situation.

Politik der Unpolitischen. Zur katholischen Liturgischen Bewegung in der Weimarer Republik - Adamik, Julie
Mit ihrem Werk Politik der Unpolitischen wirft Julie Adamik ein neues Licht auf die bislang traditionsgeschichtlich basierte Erforschung der Liturgischen Bewegung in der Weimarer Republik, indem sie die vernachlässigte politische Dimension dieser scheinbar unpolitischen Reformbewegung herausarbeitet. Der geschichtswissenschaftliche Ansatz und die damit verbundene umfassende Analyse der Quellen zeigen die komplexen Interaktionen zwischen den vier liturgisch bewegten Akteuren Romano Guardini, Abt Ildefons Herwegen, Abt Albert Schmitt sowie Theodor Abele und politischen Kontexten der Weimarer Republik. Dabei wird das Phänomen einer Politik der Unpolitischen untersucht, das sich im Kontext der Liturgischen Bewegung als destabilisierender Faktor der Weimarer Republik erweist. Das Buch bietet damit nicht nur neue Einblicke in das Selbstverständnis der Liturgischen Bewegung, sondern eröffnet darüber hinaus innovative Zugänge zu den Verflechtungen zwischen Religion und Politik.
Keywords: Liturgische Bewegung; Weimarer Republik; politischer Katholizismus; Romano Guardini; Reformbewegungen

A Memetic NSGA-III for Green Flexible Production with Real-Time Energy Costs & Emissions - Burmeister, Sascha Christian (Croatian Operational Research Review)

Reflexion – Repräsentation – Partizipation. Das Aufnahmeverfahren in das Bundesweite Verzeichnis des Immateriellen Kulturerbes und der Bewerbungsprozess des Schützenwesens - Leineweber, Jonas (Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland)

Tradition im Wandel. Dynamische Tradierung und Formierung des Kulturerbes Schützenwesen in Westfalen - Leineweber, Jonas; Becker, Peter (Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland)

Einführung - Leineweber, Jonas (Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland)